Liver lesions found at colectomy in ulcerative colitis: correlation between histological findings and biochemical parameters. Issue 11 (November 1994) - Mattila, J; Aitola, P; Matikainen, M
Abstract : AIMS--To classify lesions discovered at colectomy in patients with ulcerative colitis; to assess the importance of histological findings by correlating them with biochemical parameters. METHODS--Liver tissue specimens taken at colectomy from 59 patients with chronic ulcerative colitis were studied using light microscopy. The findings were compared with results of biochemical liver function tests. RESULTS--Abnormal laboratory findings were found in 12 patients with liver histology consistent with primary sclerosing cholangitis. Non-specific reactive hepatitis was observed in six patients, eight had fatty liver, and three minor non-specific parenchymal changes. Twenty nine patients had normal liver histology. The highest cholestatic serum enzyme activities were seen in two patients with sclerosing cholangitis. Cholangiography in these patients also revealed changes in the extrahepatic bile ducts. However, identical histological changes were also present in patients with only slightly abnormal or even normal liver enzyme activities. CONCLUSION--Biochemical tests of liver function do not reliably indicate the extent or severity of bile duct damage in ulcerative colitis, the assessment of which requires liver biopsy.